Knowledge, Attitudes, Disaster Training and Self Efficacy on Disaster Preparedness - Iyam Mariam; Johan Budhiana; Iwan Permana; Rosliana Dewi; Woro Rahmanishati; Lia Noviyanti; Rima Novianti Utami; Waqid Sanjaya; Abdul Rahman La Ede; Yohan Frans Unmehopa (Research Horizon, 2021)
This study was conducted with the aim of investigating the role of knowledge, attitudes, disaster training and self-efficacy of adolescents of Sirnaresmi Village, West Java on disaster preparedness. This study uses the qualitative method with field research in Sirnaresmi. The results showed that there was a simultaneous or shared influence on knowledge, attitudes, disaster training and self-efficacy on disaster preparedness. The results revealed that there is a relationship between the four aspects in influencing disaster preparedness. Training is needed in mitigation as a short-term educational process. It needs to be conducted by using systematic and organized ways and procedures where training participants will learn practical knowledge and skills for specific purposes. By conducting disaster training, an individual will gain knowledge and skills in dealing with disasters so that with the training carried out, knowledge about disasters will increase.